Effects of dietary soluble or insoluble fiber intake in late gestation on litter performance, milk composition, immune function, and redox status of sows around parturition. (30th October 2020) - Liu, Yang; Chen, Nan; Li, Dan; Li, Hua; Fang, Zhengfeng; Lin, Yan; Xu, Shengyu; Feng, Bin; Zhuo, Yong; Wu, De; Theil, Peter Kappel; Che, Lianqiang
Abstract: The objective of this study was to investigate the effects of dietary soluble fiber (SF ) or insoluble fiber (ISF ) intake in late gestation on litter performance, milk composition, immune function, and redox status of sows around parturition. A total of 60 Yorkshire sows were randomly assigned into three dietary treatments: normal level of dietary fiber (CON, 16.16% dietary fiber with 1.78% soluble fiber and 14.38% insoluble fiber), high insoluble fiber (ISF, 30.12% dietary fiber with 2.97% soluble fiber and 27.15% insoluble fiber), and high soluble fiber (SF, 30.15% dietary fiber with 4.57% soluble fiber and 25.58% insoluble fiber). Digestible energy and crude protein intake were comparable among treatments via adjusting feed intake from day 90 of gestation to parturition. After parturition, all sows were fed the same lactation diet. Results showed that litter performance of sows was not markedly affected by maternal fiber intake. However, sows fed ISF or SF diet had increased concentration of plasma mmunoglobulin G at day 107 ( P < 0.05) and parturition ( P < 0.01), and the SF diet had a tendency to increase fat content in both colostrum and milk relative to the CON diet. Furthermore, sows fed ISF diet had increased glutathione peroxidase activity ( P < 0.05) at day 107, but decreased the plasma level of malondialdehyde at parturition ( P < 0.05). High maternal SF intake tended to decrease the number of weaned piglets due to the increased preweaning mortality, as compared with sows fed the ISF diet. In conclusion, high fiber intake in late gestation may improve immune function and redox status, but differentially influenced the milk composition and preweaning mortality.